PERAN GURU DALAM MENUMBUHKAN KARAKTER DISIPLIN SISWA SEKOLAH DASAR MELALUI PEMBIASAAN DALAM PEMBELAJARAN - Risma; haifaturrahmah; Ineng Irma Rezkillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the teacher’s role in developing students’ discipline through habituation in elementary school learning. A qualitative descriptive approach was employed, involving teachers and fifth-grade students from an elementary school as research subjects. Data were collected through observation, interviews, and documentation. The results indicate that teachers act as role models, guides, and supervisors in instilling positive habits such as obeying classroom rules, completing tasks on time, and maintaining neatness. Habituation is implemented through daily routines, teacher modeling, reinforcement, and consistent consequences. Challenges faced by teachers include student behavior differences and lack of parental support in reinforcing discipline at home. This study highlights that consistent habituation and school environment support are crucial for shaping students’ discipline. Keywords: Teacher’s Role, Discipline, Habituation, Elementary School